Prague women's drinking before and after the 'velvet revolution' of 1989: a longitudinal study - Kubicka, L; Csémy, L; Kozený, J (Addiction (Abingdon, England), 1995)
Results are presented of a follow-up study in which a representative sample of 608 Prague women aged 20-49 years in 1987 at first interview was re-interviewed in 1992 3 years after the resolution that ended the 41 years of the Communist era in Czechoslovakia. The average yearly consumption of alcohol in the followed-up female sample increased between 1987-92 from a reported 3.6 litres to 4.8 litres. The percentage of heavier drinkers (with average daily consumption of over 20 g alcohol) increased from 7.2% to 14.0%. The women expressed increased tolerance of drunkenness in their attitudes to drinking. The consumption increase was mainly due to increased drinking frequency of spirits and to increased quantity of beer consumed per occasion. The consumption increase was largest in women working as free-lance and the newly emerging self-employed women; economically inactive women did not increase their consumption. Women who reported a positive impact of the socio-political changes on their personal lives and an expansion of social contacts also reported larger than average consumption increases. A coincidence of stressful, possibly self-inflicted, life events and increased alcohol use was observed and interpreted as probably a two-way influence.
Keywords: Alcoholism; Cross-Sectional Studies; životní styl; sociální změna; Incidence; Czechoslovakia; Middle Aged; Československo; Life Style; incidence; průřezové studie; Adult; genderová identita; alkoholismus; městské obyvatelstvo; ženské pohlaví; Social Change; Humans; lidé středního věku; Alcohol Drinking; pití alkoholu; dospělí; Urban Population; Female; lidé; Gender Identity